Suppose that the functions \( p \) and \( q \) are defined as follows. \[ \begin{array}{l}p(x)=-2 x-1 \\ q(x)=2 x^{2}+2 \\ \text { Find the following. } \\ (p \circ q)(2)=\square\end{array} \] \( (q \circ p)(2)=\square \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To find \( (p \circ q)(2) \), we first need to calculate \( q(2) \). \[ q(x) = 2x^2 + 2 \implies q(2) = 2(2)^2 + 2 = 2 \times 4 + 2 = 8 + 2 = 10. \] Now, we use this result to find \( p(q(2)) = p(10) \). \[ p(x) = -2x - 1 \implies p(10) = -2(10) - 1 = -20 - 1 = -21. \] Thus, \( (p \circ q)(2) = -21 \). Now, for \( (q \circ p)(2) \), we start with \( p(2) \). \[ p(x) = -2x - 1 \implies p(2) = -2(2) - 1 = -4 - 1 = -5. \] Next, we find \( q(p(2)) = q(-5) \). \[ q(x) = 2x^2 + 2 \implies q(-5) = 2(-5)^2 + 2 = 2 \times 25 + 2 = 50 + 2 = 52. \] Thus, \( (q \circ p)(2) = 52 \). So the final results are: \[ (p \circ q)(2) = -21 \quad \text{and} \quad (q \circ p)(2) = 52. \]